An Exploratory Study on the extent of Budgeting Practices within Small and Medium sized Enterprises and the Factors Therein - Arulanandam, Benedict Valentine; Selvan V, Dr Christo; Weng, Ling Chee (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to identify the extent of usage of budgeting practices among small and medium companies (SMEs) in Malaysia and to investigate the effect of size of firm, sophistication level of operations and level of competition, computerized accounting system, and workers participation in budgeting practices. To achieve these objectives, this research employed a questionnaire method to interpret and generate the results. Several statistical methods were used to analysis the responses, which are descriptive analysis and inferential analysis. In term of budgeting practices, the research revealed that the sales, production and purchase budget are the most heavily used among SMEs in Malaysia. In addition, the results also revealed that there are significant and positive relationship between size of firm, sophistication level of operation and level of market competition, computerized accounting system, participation of workers in budgeting practices among SMEs in Malaysia. This research provides new empirical evidences and contributes a better understanding of the use of budgeting practices among SMEs in Malaysia.